(untitled) (Journal of Health Sciences, 2014)
Introduction: The increased risk of coronary artery disease in diabetics could be explained by the lipoprotein irregularities associated with diabetes mellitus. The primary aim of this study is to examine the role of apple vinegar and syrup in the management of type 2 diabetes mellitus.Methods: The interventional study included 500 participants (195 men and 305 women) with dyslipidemia and prediabetes or type 2 diabetes mellitus, aged 50-70 years, living in Sarajevo area. Patients were recruited from 5 outpatient diabetes counselling departments and treated with natural apple vinegar and syrup supplementation over a period of five weeks. The patients have been evaluated before treatment and 5 weeks after the treatment. During the study, dosage of drugs for diabetes or prediabetes was not changed.Results: After 5 weeks of supplementation with apple vinegar and syrup waist circumference (p=0.016), total cholesterol (p=0.01), low density lipoprotein (LDL) cholesterol (p=0.008) and triglycerides (p=0.019) were significantly reduced, as well as blood pressure (-14%). Study results show decrease of mean fasting blood levels of glucose, but statistically not significant (p=0.058). The body mass index also decreased insignificantly (p=0.089). The high density lipoprotein cholesterol level was not increased significantly after supplementation (p=0.26).Conclusion: According to our results, apple vinegar has important role in reduction of total cholesterol levels, triglycerides, LDL cholesterol and waist circumference in patients with type 2 diabetes. Also, it has positive effect on blood pressure.